Selected parameters of anaerobic fitness and somatic components among Super-league team handballers playing various positions - Krawczyk, K. (Journal of Kinesiology and Exercise Sciences, 2020)
Study aim: The aim of the study was to evaluate the relative mechanical work (J/kg), maximal power (W/kg) and the time to attain (s) and of maintaining (s) power in the Wingate test among super-league handballers playing different positions. Additionally, the somatic components of the body were assessed, based on measuring body composition. Material and methods: Participants: 20 players of the super-league handball team. Mean age of the subjects - 25.84 ± 3.36 years, mean body height - 191.89 ± 12.82 cm, mean body mass - 97.99 ± 7.18 kg, mean BMI - 25.85 ± 1.91. Anaerobic fitness was assessed in accordance via the Wingate-30 s test procedure, on a Monark 824E cycle ergometer, using the MCEv5.0 software program, while body composition was assessed with the Tanita SC 330, Japan body composition analyser. Results: The mean value of the maximum power among the participants was - 11.45 ± 0.86 W/kg., mean value of the work - 256.78 ± 15.93 J/kg., the mean value of the time to attain power - 4.63 ± 0.80 s., mean value of time maintaining power - 2.91 ± 1.05 s., power decrease index - 26.17 ± 3.52%. The mean value of the FAT% index - 12.92 ± 3.27% and the mean percentage of water in the body composition - TBW% - 60.94 ± 1.99. Conclusions: The selected parameters of anaerobic fitness obtained by the participants in the Wingate test were at a good and average level, which certainly did not guarantee the achievement of high sports results in the men's handball super-league competition. Higher values of the parameters regarding anaerobic fitness were obtained by the players playing in the positions: centre and winger, relative to pivots and goalkeepers. The values of body composition tissue components were within the limits of the results for referencing.